UPAYA MEMPERSIAPKAN KOMPETENSI SUPERVISOR PADA GURU BIMBINGAN KONSELING UNTUK MENGHADAPI TANTANGAN PENDIDIKAN ISLAM PADA ERA SOCIETY 5.0 - Azwar, Beni; Seprianto, Seprianto; Hartini, Hartini (MUHAFADZAH: Jurnal Ilmiah Bimbingan dan Konseling Islam, 2022)
Education is something that is important to humans because education teaches them how to deal with all the problems in the universe and keep their lives going. Teachers of guidance and counseling have a lot on their plates. In order for teachers to meet the challenges of Islamic education in the era of society 5.0, where students are required to be able to solve problems and think critically, it is important to improve the competence of supervisors in guidance teachers and counseling. Teachers must be able to guide their students to become human beings of development with a Pancasila spirit, then have professional honesty, and always be able to maintain good relations with their students, colleagues, parents of students or families, and the community and have creativity. The method in this study is descriptive with a qualitative approach, data collection in this study using observation, interview and documentation techniques. The results of this study are that in improving the competence of guidance and counseling teacher supervisors, the school principal has a very important role so that this can be realized. Some of the programs that have been designed and scheduled by the SMPIT Annida Lubuklinggau school principal include conducting class visits, conducting individual interviews and conducting evaluations related to guidance and counseling teacher performance reports. Manusia perlu memiliki akses pendidikan untuk belajar bagaimana menghadapi semua masalah di alam semesta dan melanjutkan hidup mereka. Guru bimbingan dan konseling memiliki banyak tugas. Guru harus selalu dapat menjaga hubungan baik dengan siswanya, rekan kerja, orang tua siswa atau keluarga, dan masyarakat. Mereka juga harus mampu membimbing anak didiknya menjadi manusia pembangunan yang berjiwa pancasila., maka dari itu pentingnya dalam meningkatkan kompetensi supervisor pada guru bimbingan dan konseling supaya dapat menghadapi tantangan-tangan pendidikan Islam yang ada pada era society 5.0, dimana siswa dituntut untuk harus dapat memecahkan masalah, berpikir kritis dan memiliki kreatifitas. Adapun metode dalam penelitian ini ialah deskriptif dengan pendekatan kualitatif, pengumpulan data didalam penelitian ini dengan menggunakan teknik observasi, wawancara dan dokumentasi. Hasil dari penelitian ini ialah dalam meningkatkan kompetensi supervisor guru bimbingan dan konseling, kepala sekola memiliki peranan yang sangat penting supaya hal ini dapat terwujud. Adapun beberapa program yang telah dirancang dan dijadwalkan oleh kepala sekolah SMPIT Annida’ Lubuklinggau yaitu diantaranya seperti melakukan kegiatan kunjungan kelas, melakukan wawancara perseorangan dan melakukan evaluasi terkait laporan kinerja guru bimbingan dan konseling.